MOPIYA (Smart Monopoly of Culture) Media to Improve Elementary School Natural and Social Science Students' Learning Outcomes - Hanifah, Isna Khoiriyah Noor; Yulianto, Sigit (Jurnal Ilmiah Pendidikan dan Pembelajaran, 2025)
The limited use of learning media in the subject of science has contributed to student learning outcomes that do not meet the KKTP. This study aims to develop a MOPIYA (Monopoli Pintar Budaya) learning media for elementary school students in grade IV. This study uses a Research and Development (R&D) approach using ADDIE as its development model. The resulting product is validated by a material expert validator and a media expert validator. This study involved 25 grade IV students as research subjects. Data collection methods include interviews, observations, tests, questionnaires, and documentation. Product feasibility is evaluated through percentage analysis, while effectiveness is assessed using a normality test, t-test, and N-Gain test. The evaluation results show that the MOPIYA learning media is very feasible, scoring 93.3% from material experts and 94.3% from media experts. The t-test results revealed a significant difference in student learning outcomes before and after implementing MOPIYA media in science learning. In addition, the results of the N-Gain test showed a significant increase in student learning outcomes for small and large groups. The MOPIYA (Monopoli Pintar Budaya) learning media is feasible and effective in improving science learning outcomes for grade IV elementary school students. This study highlights the potential of the media developed to assist teachers in delivering teaching materials and students achieve learning outcomes.